Knowledge, attitude and practice towards salt intake of its associated factors among hypertensive Felda Residence in Terengganu - Wan Ain Nadirah Che Wan Mansor,; Sakinah Harith,; Che Suhaili Che Taha,; Ong, Ying Qian (Penerbit Universiti Kebangsaan Malaysia, 2021)
Hypertension in Malaysia, where at least one out of three Malaysian adults has hypertension, is a significant contributor to cardiovascular diseases. Therefore, this cross-sectional study focus to determine the prevalence of hypertension and the association of socio-demographic, anthropometry status, blood pressure, and Knowledge, Attitude, and Practice (KAP) towards salt intake with hypertension among participants in FELDA’s residence in Terengganu, Malaysia. About 94 participants from three FELDA’s in Terengganu participated in this study. The data were analyzed by SPSS. The prevalence of hypertension in this study was 39.4%. The majority of participants were females (60.6%) with a mean age of 50.3 (12.0) years old. The KAP questionnaire is given to hypertensive participants. All participants had good knowledge of salt intake. Meanwhile, the majority of the participants in the hypertensive group (70.3%) had a good attitude towards the salt intake. For the practice questions, 56.8% were categorized as lack of practice. The analysis revealed variables that significant with hypertension were aged (p=0.001), body mass index (BMI) (p=0.001), and waist circumference (p=0.001). There is also a significant association between diastolic blood pressure with gender (p=0.003). This evidence would be useful for an intervention program aimed at improving awareness, thereby reducing the incidence of hypertension among the FELDA communities.